Aortic endograft infection after thoracic endovascular aortic repair: two case reports and literature review - Peng, Danping; Xu, Guang; Wang, Bin; Li, Xin; Wang, Yang (Frontiers in Cardiovascular Medicine, 2025)
With the maturity of thoracic endovascular aortic repair (TEVAR) technology and its increasing application in clinical practice, complications and long-term management after TEVAR have become issues of concern. Here, we report two cases of TEVAR for thoracic aortic dissection. One patient developed recurrent fever 6 years after TEVAR and underwent multiple courses of antibiotic therapy with a poor response. He came to our hospital 6 months later and presented with gastrointestinal bleeding. Imaging revealed the presence of an aortic abscess around the stent graft involving the esophagus and mediastinum. The patient's condition deteriorated rapidly after admission, and he ultimately succumbed to hemorrhagic shock. Another patient developed recurrent fever 1 year after surgery. Imaging studies suggested an aortic abscess with involvement of the esophagus, and the patient chose conservative treatment. After long-term anti-infective treatment, the infected lesions remained but had decreased in size. Aortic endograft infection complicated by multiple organ involvement is a rare complication of TEVAR and has a high mortality rate. After an extended postsurgical period, patients who have undergone TEVAR often lack regular follow-up and are easily overlooked. Our cases highlight the importance of early prevention, early diagnosis, and appropriate management of late complications following TEVAR.